2010
DOI: 10.1098/rspb.2009.2134
|View full text |Cite
|
Sign up to set email alerts
|

The energetic basis of acoustic communication

Abstract: Animals produce a tremendous diversity of sounds for communication to perform life's basic functions, from courtship and parental care to defence and foraging. Explaining this diversity in sound production is important for understanding the ecology, evolution and behaviour of species. Here, we present a theory of acoustic communication that shows that much of the heterogeneity in animal vocal signals can be explained based on the energetic constraints of sound production. The models presented here yield quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 50 publications
5
134
1
Order By: Relevance
“…Tradeoffs between male traits preferred by females may be common, and may help to explain broad patterns of correlated trait evolution. For example, there is a negative correlation between call rate and duration across a large taxonomic range of acoustic animals [49], despite the fact that sexual selection commonly favours males with both faster and longer calls [50].…”
Section: Discussionmentioning
confidence: 99%
“…Tradeoffs between male traits preferred by females may be common, and may help to explain broad patterns of correlated trait evolution. For example, there is a negative correlation between call rate and duration across a large taxonomic range of acoustic animals [49], despite the fact that sexual selection commonly favours males with both faster and longer calls [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that conclusions are most firmly established if similar results appear both in contrast analyses and in analyses using species as data points (37)(38)(39). When results are presented graphically, using species has another advantage of allowing the graph to show species characteristics, such as lifestyle.…”
Section: Figmentioning
confidence: 98%
“…Acoustic communication is heavily dependent on the energy generated from metabolism [92] and may be particularly influenced by suboptimal mitochondrial function. A recent comparative study of the metabolic costs of calling revealed that the energy cost of calling in ectotherms averages eight times the resting metabolic rate [93].…”
Section: Oxidative Stress In the Twenty-first Centurymentioning
confidence: 99%